2021
DOI: 10.21203/rs.3.rs-620297/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffuse Midline Glioma with H3-K27M Mutation: A Rare Case with GFAP-positive Anucleate Whorled Patterns

Gu J2,
et al.

Abstract: Background: Diffuse midline glioma with H3-K27M mutation is a new tumor type in the 2016 WHO classification of tumors of the central nervous system, with predominantly astrocytic differentiation and is characterized by K27M mutation in either H3F3A/-HIST1H3B/C. It occurs at the midline of the CNS. It is mainly found in children, and adult cases are relatively rare . Although its histopathological features have been widely described, GFAP-positive anucleate whorled patterns have not been reported to the best of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“… 3 , 4 TMZ often promotes apoptosis by inducing the DNA damage. 5 , 6 The prognosis of many patients is not ideal as the glioma cells could acquire chemoresistance. 7 , 8 It has been revealed that low oxygen tension (hypoxia) established in growing tumor masses could induce the chemoresistance of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 TMZ often promotes apoptosis by inducing the DNA damage. 5 , 6 The prognosis of many patients is not ideal as the glioma cells could acquire chemoresistance. 7 , 8 It has been revealed that low oxygen tension (hypoxia) established in growing tumor masses could induce the chemoresistance of tumor cells.…”
Section: Introductionmentioning
confidence: 99%